Artificial intelligence and religion: between slavery and the path to salvation - Necula, Constantin Valer (Journal for the study of religions and ideologies, 2024)
The people of the XXI century seem to search for salvation in the hands of technology such as artificial intelligence, nanotechnology, internet of things etc. There is an increasing trust in the capacity of artificial intelligence to transform and transcend life and death. Unfortunately, post-humanist technologies aimed to liberate humans from all existential burdens and dilemmas challenge the liberation and salvation itself. One big question that arises in the minds of modern Christians is: Where is the hand of God in the world conquered by technology? The current paper explores the specificity of using Artificial intelligence for religious and spiritual needs and activities, focusing on the implication and limitations of AI tools in religious life. The main questions that our study addresses are: Which aspects of religious life are and may be impacted by Artificial Intelligence? What are the main limitations of AI-tools regarding individuals' spiritual needs? Can conversational AI-agents redefine the relationship with the priest? The analysis revealed that artificial intelligence needs to be addressed as a tool. It is neither ultimate doom nor the way to salvation. The wisdom of human beings has the power to liberate themselves from all the slaveries, including technology. The salvation brought by repentance and forgiveness can only be revealed through religious and spiritual development.